Media Sosial Sebagai Alat Pemasaran Mangrove Pandang Tak Jemu Di Kampung Tua Bakau Serip - Sianipar, Baktivillo; Kartika Cahayani; Okta Safitri; Bram Handoko; Dinda Aisyah Nurul Intan; M. Khori Kurnia Subagja; Silitonga, Frangky (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
Mangrove Pandang Tak Jemu in Kampung Tua Bakau Serip is a unique and interesting ecotourism destination. Considering the importance of the mangrove tree ecosystem and its potential as a tourist attraction, an effective marketing strategy is needed. One of the most effective and efficient ways to promote this destination is through social media. This article resulting from community service will explain how social media can be used as a very effective tool to market the Mangrove Pandang Tak Jemu in Kampung Tua Bakau Serip. Choosing the right media and the right marketing strategy, social media can increase visibility thereby attracting more visitors, and ultimately support the mangrove forest environment through sustainable tourism. Optimal use of social media can help Mangrove Pandang Tak Jemu in Kampung Tua Bakau Serip become a widely known tourist destination, as well as provide education and increase awareness of the importance of the mangrove ecosystem as a lungs of the world